2017
DOI: 10.1021/jacs.7b02696
|View full text |Cite
|
Sign up to set email alerts
|

Salicylideneanilines-Based Covalent Organic Frameworks as Chemoselective Molecular Sieves

Abstract: Porous materials such as covalent organic frameworks (COFs) are good candidates for molecular sieves due to the chemical diversity of their building blocks, which allows fine-tuning of their chemical and physical properties by design. Tailored synthesis of inherently functional building blocks can generate framework materials with chemoresponsivity, leading to controllable functionalities such as switchable sorption and separation. Herein, we demonstrate a chemoselective, salicylideneanilines-based COF (SA-COF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 38 publications
6
134
0
1
Order By: Relevance
“…[68] The resultant COF possesses a relatively high BET surface of 1588 m 2 g −1 with a narrow pore size centered at 1.43 nm. To demonstrate this, Loh and co-workers designed a salicylideneanilines-based COF material (SA-COF) by condensation of 1,3,5-tris(4-aminophenyl) benzene and TFP.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…[68] The resultant COF possesses a relatively high BET surface of 1588 m 2 g −1 with a narrow pore size centered at 1.43 nm. To demonstrate this, Loh and co-workers designed a salicylideneanilines-based COF material (SA-COF) by condensation of 1,3,5-tris(4-aminophenyl) benzene and TFP.…”
Section: Environmental Remediationmentioning
confidence: 99%
“…[3] Covalent organic frameworks (COFs), [6][7][8][9][10] crystallinep orousm aterials formed by the self-assembly of purely organic building blocks, have been explored for aw ide range of applications, such as optoelectronics, [11][12][13] gas storage, [14] and catalysis. [15][16][17][18][19][20][21][22] COFs have also shown promise as adsorbents for organic dyes, [23][24][25][26][27] mercury, [28,29] radionuclides, [30] and lanthanides, [31] as carriers for drug delivery, [32][33][34] and isolation of industriallyr elevant compounds. [35] Recently, we demonstrated that COFs can be used to efficientlyc apture marine toxin okadaic acid from seawater.…”
mentioning
confidence: 99%
“…Similarp henomenon hasb een recently reported by Ning et al wherein basic -NH functionality selectively interacts with the -OH groups over -NH 2 to facilitatechemoselective separation in salicylideneanilines-based COFs. [43] We further investigated the chemoselective ability of TzTz-POP-3 in the mixture as it has higher and faster uptake capacity towards -OH containing (FL) dye over -NH 2 based (FU) Dye. To wards this end, TzTz-POP-3 powderw as suspended in aqueous solution of both FL andF U ( % 50 mmol each;1 :1 ratio by vol.)…”
Section: Chemoselective Dye Adsorptionmentioning
confidence: 99%